Pastoral Care to Migrants - Thomas, P. Lawrence (Asian Horizons, 2024)
Today, migration is a prevalent and often discussed theme. Migration, both voluntary and forced, is increasing all over the world. Migration presently offers a major context for the Church’s mission of evangelization and camaraderie with the migrants. The Scriptures depict Yahweh as the God of Migrants, and Jesus, who took the form of a human being, was also to present himself as a migrant from heaven who could guide migrants to heavenly Jerusalem. His Mystical Body by all means shall be an asylum for migrants and the members of the Church have a great responsibility of accepting the migrants and sharing the mission of spreading the Good News among them with a sense that these migrants also belong to the Kingdom of God. As pilgrims journeying towards the heavenly homeland, we should be more sympathetic to all people on the move today.